Effect of protein source and protease addition on performance, blood metabolites and nutrient digestibility of turkeys fed on low-protein diets from 28 to 55 d post hatch. Issue 3 (3rd May 2016) - Shahir, M. H.; Rahimi, R.; Taheri, H. R.; Heidariniya, A.; Baradaran, N.; Asadi Kermani, Z.
Abstract: The objective of this study was to investigate the effect of a monocomponent protease and dietary inclusion of canola meal (CM) and poultry by-product meal (PBM) on growth performance, carcass characteristics and blood metabolites of turkeys fed on low crude protein (CP) diets from 28 to 55 d post hatch. Experimental treatments included control, maize–soybean meal diet including 258.3 g/kg CP; negative control 1 (NC1), maize–soybean meal diet with reduced CP (232.4 g/kg); NC2, control diet (CP, 258.3 g/kg) including CM (80 g/kg) and PBM (80 g/kg); NC3, maize–soybean meal diet with reduced CP (232.4 g/kg) including CM (80 g/kg) and PBM (80 g/kg). Also, the NC1 + P and NC3 + P diets were created by addition of protease enzyme (30 000 units/kg of diet) to the NC1 and NC3 diets, respectively. The NC3 group had lower body weight gain (BWG) compared to those fed on the control diet, and no improvement with enzyme addition (NC3 + P) was achieved. The protease addition to the NC1 diet (NC1 + P) improved BWG to the level of the control diet. The NC1 group had higher feed conversion ratio (FCR) compared to the control and NC3 + P, but protease addition to the NC1 diet improved FCR. Protease addition to the low CP diets resulted in higher nitrogen (N) retention than in the control and NC2 groups. Also, the NC1 + P and NC3 + P diets increased apparent ileal digestibility (AID) of CP compared to the control group. It was concluded that addition of CM (up to 80 g/kg) and PBM (up to 80 g/kg) to turkey diets had no negative effect on growth performance from 28 to 55 d of age. The NC1 + P group achieved the BWG of the control group which was partially due to increases in N retention and AID of CP, but the NC3 + P group failed to recover the growth losses. This difference implies that the efficacy of the protease may depend upon the protein source in the ration.